Effect of central screw taper angles on the loosening performance and fatigue characteristics of dental implants - Sun, Fei; Lv, Li-Tao; Xiang, Ding-Ding; Ba, De-Chun; Lin, Zeng; Song, Gui-Qiu (Journal of the mechanical behavior of biomedical materials, 2022)
Biomechanical performance plays an important role in the long-term service of dental implants. Loosening and fatigue damage of the central screw are the most common problems. This research investigated the effect of the central screw taper angle on the loosening performance and fatigue characteristics of dental implants. Central screws with four taper angles, 30°, 60°, 90° and 180°, were processed and tested. The loosening performance of the screws under initial and postload conditions was compared. Then, the fatigue characteristics of dental implants was measured. Finally, the wear and fracture modes of the screws were observed. The damage locations were verified by finite element analysis (FEA). The results showed that the central screws with 30° taper had substantially better anti-loosening performance and less fretting wear. The central screws with 180° taper had a higher preload, resulting in a longer fatigue life. Furthermore, the fatigue fracture of the central screw occurred at the level of the first thread position, consistent with the FEA results. In the future clinical applications, central screws with a 30° taper angle may improve anti-loosening performance and prolong fatigue life by increasing the tightening torque.
Keywords: Fretting wear; kostní šrouby; analýza metodou konečných prvků; Dental Stress Analysis; Dental implant; točivý moment; Dental Implants; Fatigue damage; Finite Element Analysis; Torque; analýza zatížení zubů; Bone Screws; Screw loosening; Central screw; zubní implantáty